If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -74 = -110 + 6x Solving -74 = -110 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -74 + -6x = -110 + 6x + -6x Combine like terms: 6x + -6x = 0 -74 + -6x = -110 + 0 -74 + -6x = -110 Add '74' to each side of the equation. -74 + 74 + -6x = -110 + 74 Combine like terms: -74 + 74 = 0 0 + -6x = -110 + 74 -6x = -110 + 74 Combine like terms: -110 + 74 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 14+6=2(5+7v)-4 | | 10n+5=5n+25 | | 5x-126=135-4x | | 9x-(x+22)=3x+3 | | 9x+10-5x=-12 | | 4+4b-3b=2+3b | | 3x+13=5x-3 | | 16-4=3(2-x) | | 7x+-7=12x+13 | | -3x+7y+14=0 | | 6x+68=2x-36 | | -4(-4X+6)=9 | | -117+12x=3x+90 | | 3(x+1)+x=x+8 | | 2(x+2)-6x=12 | | -2+3x+6-8x=-5 | | 2500=.5m | | x-57-57=-57 | | 5-4x+3=12 | | y=5(x-1) | | 14-13=5(1+4m)-2m | | -12+6x=12+8x | | 12p-7=-3p-8 | | 5x-4x-3=7 | | 16x+14=16+x | | 4(x+5)=4(2-x) | | X+6X-3(X-4)=4(X+2) | | 3x+10=5x-22 | | 3(x+1)+x=x-8 | | 4cosx+7=0 | | 8x-5x=10+5x | | 2x+4-x=10 |